Assessment of a treadmill speed incline conversion chart: A validation study - Foreman, N. A.; Lee, E. J.; Lundstrom, C. J. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To investigate the validity of a treadmill speed incline conversion chart using physiological and subjective measures. Methods: Two groups of experienced runners (SLOW and FAST: divided based on their easy run pace) ran 6 speed incline combinations for 5 minutes each. Stages were equivalent according to the HillRunner.com chart, and stage order was randomized. Due to limitations of the chart, SLOW (n = 11) ran at inclines up to 4%, while FAST (n = 22) ran at inclines up 10%. Oxygen consumption (VO2), respiratory exchange ratio, heart rate, blood lactate, overall rating of perceived exertion (RPE), and leg RPE were measured for each stage. VO2 was compared against the VO2 predicted by the American College of Sports Medicine (ACSM) equation (ACSM VO2). Repeated-measures analysis of variance was used to detect differences between stages and inclines, and Hedges g was used as a measure of effect size. Results: Pooled results (0%-4%, N = 33) showed no incline effect on VO2, respiratory exchange ratio, heart rate, blood lactate, or RPE (P > .05; np^2 =.198), validating the chart at these inclines. At or above 6%, meaningful and significant increases occur in VO2 (g > 0.9, P < .05), with increases in heart rate, blood lactate, and leg RPE at higher inclines. ACSM VO2 underestimated oxygen consumption at all inclines up to 8% (P < .05) but not at 10% (45.9 [4.0] vs 46.7 [2.4] mL·kg-1·min-1; P = .186). Conclusion: The HillRunner.com chart is only valid at or below 4%. At higher inclines, supposedly equivalent stages result in increased exercise intensity. ACSM VO2 underestimates VO2 in trained runners at inclines up to 8%.